Conceptual map in face-to-face teaching during the coronavirus pandemic: experience report (Research, Society and Development, 2021)
Objective: to report the experience of creating a conceptual map in face-to-face teaching during the coronavirus pandemic. Methodology: this is a descriptive-exploratory study of the type of experience report. Results: Both in the face-to-face and virtual class, the students showed total interest and willingness to participate in the proposed activities. In the first class held in person, students were able to expand their knowledge and integration using various tools encouraging the use of creativity through the use of pens, paints, colored pencils, promoting the interaction of students who at the end could share their work and perform a self assessment. In remote classes, virtual platforms were used to carry out the activity, also divided into groups, even though students could remotely exercise the integration dialogue. In this way, we can see that the use of concept maps together with the practice of active learning becomes positive both in the remote environment and in person, helping to understand concepts. Conclusion: We conclude that the use of the conceptual map in conjunction with active learning helps in the development of an educational environment both in person and in a pleasant virtual environment, capable of promoting integration, critical thinking and autonomy among students.